Analisis Coeffisient Of Peformance (COP) Dan Energy Efficiency Ratio (EER) Pada AC Split Inverter Kapasitas Â½ PK Dengan Menggunakan Freon R-22 dan Freon R-32 - amir amir; Rofiroh Rofiroh; Choirus Syahri Romadhon (Universitas Muhammadiyah Tangerang, 2023)
Air conditioner (AC) is a tool used to condition the air in a room or product temperature. Air conditioning in the form of regulating temperature, regulating cleanliness, and adjusting the air flow rate. The purpose of this study is obtain the comparison of the coeffisient of peformance (COP) and Energy Efficiency Ratio (EER) values in inverter split air conditioners with a capacity of 1/2 pk using R-22 and R-32 refrigerants. The method used in this study is observation and exsperiment , data collection based on test results using ac trainers that we make, using different refrigerants or refrigerants, namely R-22 and R-32 refrigerants, by varying the rotation of the evaporator fan in low, medium, and high modes. The results of this study are in the air conditioner (AC) split inverter capacity of 1/2 pk using R-22 refrigerant the highest coeffisient of peformance (COP) value obtained by 5.05 at the turn of the high evaporator fan and coeffisient of peformance (COP) in the air conditioner (AC) split inverter capacity of 1/2 pk using the highest R-32 refrigerant obtained by 7.37 in the high evaporator fan speed variant. Then the Energy Efficiency Ratio (EER) value produced in the air conditioner (AC) split inverter capacity of 1/2 pk using R-22 refrigerant is 17.22 Btu / h, while in the air conditioner (AC) split inverter capacity of 1/2 pk using R-32 refrigerant obtained 25.13 Btu / h. So that the performance of air conditioner (AC) split inverter capacity of 1/2 pk with refrigerant R-32 has better performance compared to air conditioner (AC) split inverter capacity of 1/2 pk with refrigerant R-22.